Prosthetic abutment influences bone biomechanical behavior of immediately loaded implants - CAMARGOS,Germana de Villa (2016)
Abstract This study aimed to evaluate the influence of the type of prosthetic abutment associated to different implant connection on bone biomechanical behavior of immediately and delayed loaded implants. Computed tomography-based finite element models comprising a mandible with a single molar implant were created with different types of prosthetic abutment (UCLA or conical), implant connection (external hexagon, EH or internal hexagon, IH), and occlusal loading (axial or oblique), for both immediately and delayed loaded implants. Analysis of variance at 95%CI was used to evaluate the peak maximum principal stress and strain in bone after applying a 100 N occlusal load. The results showed that the type of prosthetic abutment influences bone stress/strain in only immediately loaded implants. Attachment of conical abutments to IH implants exhibited the best biomechanical behavior, with optimal distribution and dissipation of the load in peri-implant bone.